Effect of Hydroxy Gas Enrichment and Higher Biodiesel Concentration on Diesel Engine Performance - Asnawi Asnawi; Muhammad Muhammad; Reza Putra; Nurul Islami (Automotive Experiences, 2025)
The hydroxy gas enrichment as an additive of biodiesel fuel for internal combustion engines affected the combustion characteristics. Hydroxy gas can be produced through water electrolysis to produce hydrogen and oxygen, significantly enhancing the combustion rate. This combined effect increased efficiency, reduced pollution, and improved air quality. This study aims to determine the impact of hydroxy enrichment generated from water electrolysis on engine performance with biodiesel-diesel fuel blends. The experimental work was conducted under diverse operating conditions and tested on a 418 cc single-cylinder engine. Experiments have been performed at a constant hydroxy gas flow rate of 500 mL/min and a constant speed of 2000 rpm under various torques. The result shows that B30 and B40 without hydroxy gas decreased diesel engine performance across various engine torque. The addition of hydroxy has been observed to positively impact the combustion reaction and increase the energy conversion efficiency of diesel engines. Compared to pure diesel fuel, the efficiency of B30 and B40 decreased by 9.26% and 11.59%, respectively. The enrichment of hydroxy gas increases the engine efficiency by an average increase of all torque to 7.95% for B30H (B30 with hydroxy) and 8.68% for B40H (B40 with hydroxy). Therefore, compared to pure diesel fuel, the efficiency slightly decreases by an average of 1.31% for B30H and 2.91% for B40H at all tested torques. This phenomenon indicates that the presence of hydroxy gas in a diesel engine increases the stability of the combustion process, which results in higher cylinder pressure with lower energy input.